1989
DOI: 10.1080/00332747.1989.11024467
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Onset PTSD among Israeli Veterans of the 1982 Lebanon War

Abstract: This is an exploratory study of the nature, course and rates of delayed post-traumatic stress disorder (PTSD). We reviewed 150 medical files of Israeli soldiers who sought help between 6 months and 5 years after the 1982 Lebanon War. Results indicated that only 10% of the cases were truly examples of delayed PTSD; in a large proportion of the cases, help-seeking rather than onset was delayed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 13 publications
4
21
0
Order By: Relevance
“…An anecdotal finding from the interviews implies that the vast majority of men diagnosed with PTSD reported experiencing subsyndromal levels of symptoms for quite sometime before exacerbation to a noticeable dysfunction occurred shortly after discharge (Caspi, Saroff, Suleimani, & Klein, submitted manuscript). Whether this relates to the phenomenon of delayed PTSD requires further investigation; some researchers suggest that the delay is actually in the helpseeking rather than the onset of PTSD (Solomon, Kotler, Shalev, & Lin, 1989), whereas others view partial or subthreshold diagnoses as potential risk factors for delayedonset PTSD (Carty, O'Donnell, & Creamer, 2006). The latter view is reinforced by our findings of a subgroup of men, still in service, yet with elevated health problems, health-related impairment in functioning, and increased medical service utilization that scored above the cut-off point on the SPTSS, but did not receive a SCID diagnosis of PTSD.…”
Section: Discussionmentioning
confidence: 96%
“…An anecdotal finding from the interviews implies that the vast majority of men diagnosed with PTSD reported experiencing subsyndromal levels of symptoms for quite sometime before exacerbation to a noticeable dysfunction occurred shortly after discharge (Caspi, Saroff, Suleimani, & Klein, submitted manuscript). Whether this relates to the phenomenon of delayed PTSD requires further investigation; some researchers suggest that the delay is actually in the helpseeking rather than the onset of PTSD (Solomon, Kotler, Shalev, & Lin, 1989), whereas others view partial or subthreshold diagnoses as potential risk factors for delayedonset PTSD (Carty, O'Donnell, & Creamer, 2006). The latter view is reinforced by our findings of a subgroup of men, still in service, yet with elevated health problems, health-related impairment in functioning, and increased medical service utilization that scored above the cut-off point on the SPTSS, but did not receive a SCID diagnosis of PTSD.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, the realization that PTSD symptoms, if they occur at all, erupt immediately following exposure to trauma was an important reason for including acute stress disorder in DSM-IV. Almost all cases of apparent delayed onset PTSD turn out to involve either delayed help-seeking or subsyndromic PTSD intensified by exposure to another stressor (Solomon, Kotler, Shalev, & Lin, 1989). Pure cases of delayed onset-exposure to trauma followed by a long period of good adjustment that precedes full-blown emergence of the disorder-are rare to nonexistent.…”
Section: Whatever Happened To Delayed Onset Ptsd?mentioning
confidence: 99%
“…Therefore, it is not clear how to interpret earlier findings. It has been argued by some that delayed onset of PTSD should be labeled delayed recognition or delayed help seeking (Bramsen, 1995;Pary, Turns, & Tobias, 1986;Solomon, Kotler, Shalev, & Lin, 1989). This interpretation is supported by empirical studies that have shown that PTSD is mainly a chronic condition (Kessler, Sonnega, Bromet, Hughes, & Nelson, 1995) and that true late onset or reactivation seems to be rare (Port, Engdahl, & Frazier, 2001;Robinson et al, 1990;Solomon et al, 1989).…”
mentioning
confidence: 89%